Pengembangan Sistem Konsultasi Gizi dan Konsumsi Harian berbasis Web - Moch Alyur Ridho; Fajar Pradana; Yuita Arum Sari (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2021)
The adequacy of nutritional needs in the human body is very important in supporting its survival. Lack of nutritional needs can lead to reduced immunity to disease infections. The nutritional needs needed to meet each individual's daily calories vary greatly, it is usually supported by differences in gender and age, weight and height, the latter is a daily body activity. The difficulty of the community in determining the number of daily calories needed, the many factors that influence in the fulfillment of nutritional needs can be easily solved by the development of the system to be carried out. In addition, the user will be facilitated by the presence of several reminder features that will record the calories of food entered in his body by identifying images of food consumed by the user, and users can also consult with nutritionists available on the system to conduct further discussions. The development method conducted in this study uses waterfall method by applying Object Oriented Programming (OOP) based programming and using HTML and PHP programming languages, while to implement data structures using relational database mechanisms namely is MySQL. In this study, 3 samples were used to test the unit and produce a system that was made to run well, in addition to validation testing using 14 test cases and showing 14 functions run well.